MicroED data collection and processing. Issue 4 (1st July 2015) - Hattne, Johan; Reyes, Francis E.; Nannenga, Brent L.; Shi, Dan; de la Cruz, M. Jason; Leslie, Andrew G. W.; Gonen, Tamir
<x xml:space="preserve">Abstract</x> MicroED, a method at the intersection of X‐ray crystallography and electron cryo‐microscopy, has rapidly progressed by exploiting advances in both fields and has already been successfully employed to determine the atomic structures of several proteins from sub‐micron‐sized, three‐dimensional crystals. A major limiting factor in X‐ray crystallography is the requirement for large and well ordered crystals. By permitting electron diffraction patterns to be collected from much smaller crystals, or even single well ordered domains of large crystals composed of several small mosaic blocks, MicroED has the potential to overcome the limiting size requirement and enable structural studies on difficult‐to‐crystallize samples. This communication details the steps for sample preparation, data collection and reduction necessary to obtain refined, high‐resolution, three‐dimensional models by MicroED, and presents some of its unique challenges.